Exploring Dual Language Program (DLP) science teachers perceptions and experiences of curriculum change - Mohamad Nasri, Nurfaradilla; Mohamad Yunus, Sarah; Syed Abdullah, Sharifah Intan Sharina (Human Resource Management Academic Research Society, 2018)
A review of the literature in Dual Language Programme (DLP) revealed a very limited number of studies investigated the perceptions of DLP science teachers with regards to curriculum change, not to mention the lack of attempt to discover teachers' experiences of curriculum change. This qualitative study was designed to explore (i) Malaysia DLP science teachers' perceptions of curriculum change, and (ii) Malaysia DLP science teachers' experiences of implementing DLP science teaching. Twenty Malaysia DLP science teachers were interviewed to obtain their views on DLP. A point to note, this study does not attempt to make any generalisations, but rather provides an insight into the DLP science teachers' perceptions and experiences of curriculum change. A constructivist grounded theory approach was used to inform the methodological framework of this study, whilst a hybrid inductive and deductive analysis approach was used to analyse the interview data. Informed by the existing literature, and derived from analysis of the interview data, three themes emerged: (a) educator as co-learner, (b) ever-increasing workload, and (c) school and parent support. This study suggest the shift of teachers' role as co-learner can be explored further as an idea that could possibly contribute to deeper understanding in bilingual teaching paradigm.